2023
DOI: 10.1039/d2cy01734b
|View full text |Cite
|
Sign up to set email alerts
|

A tertiary phosphine oxide ligand-based recyclable system for the Suzuki–Miyaura and Negishi reactions: evidence for pseudo-homogeneous catalysis

Abstract: A recoverable catalyst system has been developed and its application in both Suzuki-Miyaura and Negishi coupling reactions has been demonstrated. We have also investigated the nature of the active catalyst...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…We suspect the proposal to mix these compounds arises as an artifact of making a combinatorial array (phactor) out of the popular Pd complex and ligand choices from the literature (ChatGPT). Nonetheless, the observation that this “cocktail” of ligands was the most productive result could be supported by related reports of “cocktail” catalysis in the Buchwald–Hartwig coupling. …”
Section: Resultssupporting
confidence: 59%
“…We suspect the proposal to mix these compounds arises as an artifact of making a combinatorial array (phactor) out of the popular Pd complex and ligand choices from the literature (ChatGPT). Nonetheless, the observation that this “cocktail” of ligands was the most productive result could be supported by related reports of “cocktail” catalysis in the Buchwald–Hartwig coupling. …”
Section: Resultssupporting
confidence: 59%
“…Thus, the bound SiAu 5 cluster lowers the activation energy barrier for CO oxidation, and the reaction occurs more readily compared with the Au 6 cluster process. In addition, we also noted that the reactivity and catalytical effects are also affected by supports for different metal oxide surfaces [ 5 , 9 , 20 ]. Moreover, experimental investigations are important for understanding CO oxidation on SiAu n clusters.…”
Section: Resultsmentioning
confidence: 99%
“…Metal clusters have long been extensively studied due to their unique optical, electronic, and mechanical properties, as well as their wide range of applications in catalysts [ 1 , 2 , 3 , 4 ]. Among the various types of metal clusters, Au clusters have attracted much attention as size-tunable prototypes, because they have been shown to have significant catalytic activity [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. Chen et al [ 20 ] showed that Au loading and the Au particle size have significant effects on the generation of methanol and CO; with an increase in the Au loading/Au particle size, the generation activity (Au-mass-normalized reaction rate, TOF) for methanol and CO decreases, while the selectivity for methanol generation increases.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, to obtain a good yield of the desired cross-coupled product, the reaction was studied by varying different reaction parameters. Literature reports suggest that the solvent system plays a vital role in the SMCC reaction. ,, Hence using the same amount of substrate, catalyst, and base, the reaction was performed in different organic solvents at room temperature. The solvent optimization graph depicted in Figure S7 suggested that CH 3 OH was more suitable in comparison to other solvents like EtOH, CH 3 CN, and isopropanol for this particular reaction under these conditions.…”
Section: Catalytic Studymentioning
confidence: 99%